2022
DOI: 10.1007/s11883-022-01004-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Gaps in Assessments of the Healthiness of Online Supermarkets Highlight the Need for New Monitoring Tools: a Systematic Review

Abstract: Purpose of Review Online grocery shopping is increasingly popular, but the extent to which these food environments encourage healthy or unhealthy purchases is unclear. This review identifies studies assessing the healthiness of real-world online supermarkets and frameworks to support future efforts. Recent Findings A total of 18 studies were included and 17 assessed aspects of online supermarkets. Pricing and promotional strategies were commonly applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…For example, a study conducted in 2011 Australia found that traffic-light nutrition information, a labeling approach that uses color coded information to display a product’s levels of fat, sugar, and sodium, did not influence online grocery sales [ 64 ]. However, the more recent studies included in the current review that focused on nutrition labeling found that it led to healthier food purchases, which is an especially salient finding given that several recent studies have pointed to online grocery stores’ failures to provide even required nutritional information in the United States [ 8 , 65 , 66 ] and elsewhere [ 67 ]. In one study, a web-browser extension was developed and used to display the Nutri-Score as participants shopped online [ 51 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…For example, a study conducted in 2011 Australia found that traffic-light nutrition information, a labeling approach that uses color coded information to display a product’s levels of fat, sugar, and sodium, did not influence online grocery sales [ 64 ]. However, the more recent studies included in the current review that focused on nutrition labeling found that it led to healthier food purchases, which is an especially salient finding given that several recent studies have pointed to online grocery stores’ failures to provide even required nutritional information in the United States [ 8 , 65 , 66 ] and elsewhere [ 67 ]. In one study, a web-browser extension was developed and used to display the Nutri-Score as participants shopped online [ 51 ].…”
Section: Discussionmentioning
confidence: 96%
“…This project systematically reviewed the scholarly literature to identify studies on how food marketing strategies used in online grocery shopping platforms influence consumer food preferences and food purchases and to consider the implications of the findings from these studies for WIC online ordering. In doing so, our paper contributes to the emerging literature on the characteristics of online shopping environments [ 6 , 8 ] and the marketing practices of online retailers, which include sophisticated algorithms that make product recommendations; promotions that indicate that items are scarce (going fast) or abundant (buy many at a lower price); and advertisements and promotions designed to increase related-item purchases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an urgent need for diagnostic and therapeutic options in this area. [277,278] Endogenous biomarkers, including small molecules, enzymes, cell receptors, and cytokines, are involved in the pathological process of CVD and can be exploited as stimuli to trigger in situ assembly/ disassembly of nanomaterials or as targets to guide the enrichment of nanomaterials in the lesion area. [279][280][281] These endogenous biomarker-responsive nanomaterials not only nicely circumvent the issues with CVD theranostics, such as off-target effects, short blood circulation, low bioavailability, poor solubility, and nonspecific distribution but also improve the targetability of drug delivery, accuracy of detection, imaging diagnostic capability and therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%